The Medical Burden of Heart Failure: A Comparative Delineation with Cancer in Brazil - Almeida,Dirceu Rodrigues de (2022)
Abstract Background: Due to its poor prognosis and mortality rates, heart failure (HF) has been recognized as a malignant condition, comparable to some cancers in developed countries. Objectives: To compare mortality from HF and prevalent cancers using data from a nationwide database in Brazil. Methods: This was a descriptive, cross-sectional study using secondary data obtained from Brazilian administrative databases of death records and hospitalization claims maintained by the Ministry of Health. Data were analyzed according to main diagnosis, year of occurrence (2005-2015), sex and age group. Descriptive analyses of absolute number of events, hospitalization rate, mortality rate, and in-hospital mortality rate were performed. Results: The selected cancers accounted for higher mortality, lower hospitalization and higher in-hospital mortality rates than HF. In a group analysis, HF showed mortality rates of 100-150 per 100,000 inhabitants over the period, lower than the selected cancers. However, HF had a higher mortality rate than each type of cancer, even when compared to the most prevalent and deadly ones. Regarding hospitalization rates, HF was associated with a higher risk of hospitalization when compared to cancer-related conditions as a group. Conclusions: Our findings indicate that HF has an important impact on mortality, hospitalization and in-hospital mortality, comparable to or even worse than some types of cancer, representing a potential burden to the healthcare system.